Resistance of the fiber-derived geotextile from Typha domingensis submitted to field degradation - Francisco Sandro Rodrigues Holanda; Luiz Diego Vidal Santos; Jeangela Carla Rodrigues De Melo; Gizelio Menezes Boge; Eliana Midori Sussuchi; Brenno Lima Nascimento; Marcos Vinícius Quirino dos Santos; Marla Ibrahim Uehbe de Oliveira (Scientific Reports, 2024)
Abstract Geotextiles made from plant fibers creates a suitable environment for plant growth as part of soil bioengineering techniques. The faster decomposition of plant fiber geotextiles compared to synthetic ones demands the use of composites that enhance their waterproofing and extend their durability in the environment. The objective of this work was to evaluate the resistance of a geotextile made with Thypha domingensis to degradation caused by climatic variables. Tensile strength tests were conducted in the laboratory in order to evaluate the degradation of geotextiles treated with single and double layers of waterproofing resin. Based on Scanning Electron Microscopy (SEM) images, it was verified that applying double layer of waterproofing resin delays the fibers degradation up to 120 days of exposure to the effects of climatic variables other than temperature. The maximum resistance losses due to the geotextile's exposure to degradation were statistically significant for all three treatments: control-without waterproofing resin, with one layer resin, and with two layers resin. Therefore, waterproofing resin, provides a long-term protective solution for geotextiles made from cattail fibers.